The Value of lncRNAs as a Biomarker for the Diagnosis of Gestational Diabetes: A Meta-Analysis - Fan, Yang; Chen, Xin; Yang, Song; Tu, Hongxia; Zhang, Youyi; Wang, Mingyi; Jiang, Jingying (Hormone and Metabolic Research, 2024)
Gestational diabetes mellitus (GDM) is a common metabolic disorder in pregnancy and leads to serious harm to the mother and the fetus. A variety of lncRNAs play a key role in GDM. This meta-analysis was performed to explore the potential value of lncRNAs in GDM diagnosis. Articles correlated with lncRNA and GDM were screened from Embase, Medline, EBSCO, PubMed, Chinese National Knowledge Infrastructure, and WanFang databases. Summary receiver operator characteristic (SROC) was performed to evaluate the pooled area under curve (AUC). Forest plot was conducted to calculate the sensitivity, specificity, diagnostic likelihood ratio (LR), diagnostic score, and diagnostic odds ratio (DOR). Deeks’ funnel plot was utilized to evaluate the publication bias. Eleven articles containing 12 tests (1060 GDM patients and 1066 controls) were included in this meta-analysis. AUC (0.89, 95%CI=0.86–0.92), sensitivity (0.84, 95%CI=0.80–0.87), and specificity (0.81, 95%CI=0.77–0.85)of the SROC curve showed a high diagnostic value of lncRNA for GDM. Positive LR (PLR 4.40, 95%CI=3.45–5.60) and negative LR (NLR 0.20, 95%CI=0.15–0.26) results indicated that the diagnosis of lncRNA for GDM had low clinical utility. Diagnostic score (3.09, 95%CI=2.62–3.57) and DOR (22.04, 95%CI=13.68–35.51) results suggested lncRNAs have good discriminative effect on GDM. Heterogeneity was significantly higher, but not induced by the subgroups. LncRNAs had high diagnostic value and good discriminative effect for GDM, but the clinical utility was not high. This meta-analysis study offers a potential target for GDM diagnosis.
Keywords: gestational diabetes mellitus; diagnosis; SROC